BIOSINTESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK AIR DAUN KECEMCEM (Spondias pinnata (L.f) Kurz.) DENGAN VARIASI KONSENTRASI EKSTRAK DAN SUHU SINTESIS - Ngurah Wijaya Putra; Gusti Ayu Dewi Lestari (ALOTROP, 2024)
This research aims to synthesize silver nanoparticles using various variations in extract concentration and synthesis temperature to produce the smallest and most stable silver nanoparticle. Step of this research are phytochemical screening of kecemcem leaf water extract, synthesis of silver nanoparticles with an extract concentration of 0.5; 0.75 and 1% and synthesis temperature 25; 40 and 60⁰C, and characterization of silver nanoparticles. The results of the UV-Vis spectrophotometer showed the formation of NPAg with a maximum wavelength of 420 nm. SEM and TEM results show that NPAg powder tends to clump and has an irregular round shape. PSA results show that the smallest size of NPAg is 30.55 nm with a PdI of 0.497. XRD results show that the crystal size of the synthesized NPAg is 0.23 nm.